A Facile Synthesis of 5'-Fluoro-5'-deoxyacadesine (5'-F-AICAR): A Novel Non-phosphorylable AICAR Analogue - Luciano Mayol (Molecules, 2012)
The substitution of a hydroxyl group by a fluorine atom in a potential drug is an efficient reaction that can, in principle, improve its pharmacological properties. Herein, the synthesis of the novel compound 5′-fluoro-5′-deoxyacadesine (5′-F-AICAR), a strict analogue of AICAR that cannot be 5′-phosphorylated to ZMP by cellular kinases, is reported.